2014
DOI: 10.1002/ejoc.201402805
|View full text |Cite
|
Sign up to set email alerts
|

2‐Nitroglycals: Versatile Building Blocks for the Synthesis of 2‐Aminoglycosides

Abstract: Abstract2‐Deoxy‐2‐amino‐substituted glycosides are ubiquitous compounds in biochemistry and biology. Therefore, the development of new synthetic pathways to access natural and non‐natural derivatives is highly desirable. In that context, 2‐nitroglycals appeared as versatile building blocks for reaching those targets. Since their first introduction almost forty years ago, their synthetic utility has been widely demonstrated and they have been used to access natural and non‐natural compounds with potent biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…[13] However, only a few studies have reported the synthesis of 2-nitro-2,3-unsaturated glycosides [14] from 2nitroglycal. [15] Vankar et al synthesized 2-nitro-2,3-unsaturated glycosides by using DMAP as an effective catalyst, and provided 10 substrates. Thus, efforts are still needed to develop a general methodology that can provide a direct and rapid access to 2nitro-2,3-unsaturated glycosides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] However, only a few studies have reported the synthesis of 2-nitro-2,3-unsaturated glycosides [14] from 2nitroglycal. [15] Vankar et al synthesized 2-nitro-2,3-unsaturated glycosides by using DMAP as an effective catalyst, and provided 10 substrates. Thus, efforts are still needed to develop a general methodology that can provide a direct and rapid access to 2nitro-2,3-unsaturated glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…The Ferrier rearrangement of glycals is the most common methodology to obtain these glycosides [13] . However, only a few studies have reported the synthesis of 2‐nitro‐2,3‐unsaturated glycosides [14] from 2‐nitroglycal [15] . Vankar et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, despite many efforts in the area, the synthesis of 1,2- cis aminoglycosides still remains particularly difficult since most common N -protecting groups (e.g., amides, carbamates) exhibit 1,2- trans -directing behavior during the glycosylation reaction favoring the formation of β-linked products . 2-Nitroglycals have been shown to be useful glycosyl donors for the synthesis of aminoglycosides whereby the nitro group serves as a nonparticipating latent amino functionality. Base-catalyzed conjugation of alcohols to 2-nitroglycals has been reported by the Schmidt group for forming α- and β-linked 2-amino-2-deoxy- O -glycosides . Moreover, the α/β-selectivity of this concatenation reaction is highly dependent on the nature of the base and nucleophile employed in the reaction. , …”
mentioning
confidence: 99%
“…Despite several attempts, alkylation with some methylating agents (MeI/AgNO 3 , MeOTf, Meerwein's salt) or halogenation with N ‐halogenosuccinimides were unsuccessful. 2‐Nitroglycals have been recognized as very useful glycosyl donors for Michael additions, Diels‐Alder reactions, or [3+2] cycloadditions . However, nitration of thioglycal 3 , under various experimental conditions, did not work.…”
Section: Resultsmentioning
confidence: 99%